Suppressed Programmed Death 1 Expression on CD4+ and CD8+ T Cells in Psoriatic Patients - Bartosińska, Joanna; Zakrzewska, Ewelina; Raczkiewicz, Dorota; Purkot, Joanna; Michalak-Stoma, Anna; Kowal, Małgorzata; Krasowska, Dorota; Chodorowska, Grażyna; Giannopoulos, Krzysztof (Mediators of Inflammation, 2017)
Psoriasis is a chronic inflammatory disease mediated by T cell immunity. Programmed death 1 (PD-1), a coinhibitory receptor, plays an important role in immune regulation and maintaining peripheral tolerance. The aim of the study was to compare the expression of PD-1 on the peripheral T cells between psoriatic patients and healthy controls. The study included 75 psoriatic patients and 52 healthy volunteers. The percentages and absolute numbers of CD3+, CD4+, CD8+, CD4+PD-1+, and CD8+PD-1+ T cells were analyzed using flow cytometry. The absolute numbers and percentages of CD4+PD-1+ and CD8+PD-1+ T cells were significantly decreased in the psoriatic patients in comparison with the control group. No significant correlations were found between the absolute numbers and percentages of CD4+PD-1+ or CD8+PD-1+ T cells and clinical characteristics of psoriasis. Decreased PD-1 expression on the T cells may be responsible for impaired negative regulation of immune response in psoriasis pathogenesis.